Synthesis, characterization and application of menthol-based low transition temperature mixtures for the vortex- assisted dispersive liquid-liquid microextraction of pyrethroids from water samples / Siti Amira Mat Hussin - Siti Amira , Mat Hussin (2022)
In this study, three newly menthol-based natural low transition temperature mixtures (LTTMs) were successfully synthesized. DL-menthol as hydrogen bond acceptor (HBA) meanwhile thymol, sesamol and 3-hydroxybenzoic acid were selected as hydrogen bond donor (HBD). The characterization of LTTMs was monitored and studied by polarizing optical microscopy (POM), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), and Nuclear Magnetic Resonance (NMR). In addition, density, viscosity and water content of LTTMs were determined to analyse their solvent characteristics. Thermogravimetric analysis (TGA) was studied to identify the thermal stability. These LTTMs have been applied as green extraction solvents in vortex-assisted dispersive liquid-liquid microextraction (VA-DLLME) for the extraction of pyrethroid pesticides determined by high-performance liquid chromatography with a diode-array detector (HPLC-DAD). Several key parameters that affect pyrethroid extraction efficiency were identified and optimized. After optimization, the LTTM-VA-DLLME method was found to be able to detect pyrethroids in the range of 0.5 - 1000.0 μg L-1 with good linearity (R2 = 0.9988-0.9995). The relative standard deviation of inter-day and intra-day precisions were 2.2 - 5.0 % (n = 5) and 1.2 - 1.9% (n = 7) respectively. The limit of detection (LODs) and limit of quantification (LOQs) were in the range of 0.05 - 0.10 μg L-1 and 0.18 - 0.35 μg L-1, respectively. The optimized method can successfully determine pyrethroids in water samples with good recoveries of 73–111%.